Relationship between Adverse Childhood Experiences and Daily Stress Responses: Moderating Roles of Pet Attachment and Coping Strategies among Pet Owners - Azam, Hooria; Ehsan, Neelam; Rehman, Fiza (Pakistan Journal of Humanities and Social Sciences, 2025)
The purpose of the study was to investigate the relationship between adverse childhood experiences (ACEs) and daily stress responses, focusing on the moderating roles of pet attachment and coping strategies among pet owners residing in Rawalpindi and Islamabad, Pakistan. A sample of 130 individuals aged 20 to 37 years, were collected through snowball sampling technique. The study employs of self-report measures, including the Adverse Childhood Experiences (ACEs) Questionnaire, the Daily Stress Response Scale (DSRS), The Scale of Comfort from Companion Animal (CCAS), and the Coping Scale (CS). Descriptive, correlational and regression analyses were computed to analyze the relationship between adverse childhood experiences, daily stress response, and the moderating roles of pet attachment and coping strategies. The results of the study suggested a significant positive correlation between ACEs and daily stress responses, supporting the hypothesis that individuals with a history of ACEs experience elevated stress. The regression analysis demonstrated that the coping strategies and pet attachment significantly moderated the relationship between ACEs and daily stress responses. These finding further suggest that emotional support from pets and effective coping mechanisms can guard the adverse and negative effects of childhood experiences on daily stress responses, in the adulthood. The study focused on the importance of pet attachment and coping strategies in reducing increased stress, particularly for individuals which are affected by ACEs. This research highlights the importance of applying early interventions for individuals with adverse childhood experiences (ACEs) which is essential in reducing the risk of long-term negative impacts on stress regulation and overall mental well-being.